Intervening in Informal Learning: Activity theory as teaching tool - Carter, Susan (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2013)
In this article, I argue that a concentrated focus on everyday informal learning about unions is critical not only to re-thinking union education programs, but to the overall project of union renewal. The article offers, by way of example, an inquiry into the grievance system as a routine (and central) union practice and a key site of informal learning. This inquiry is directed by cultural historical activity theory (CHAT) which provides method, tools, and theoretical building blocks for better understanding everyday learning. In addition, I argue, CHAT presents a powerful pedagogical tool for educators, leaders, and activists who are concerned with the challenge of intervening critically and strategically into everyday learning and everyday practices of unions and their members.